Petko Todorov’s plays and the poetics of European Symbolism (Colloquia Comparativa Litterarum, 2025)
The paper examines Petko Todorov’s five symbolist plays (Masons, Strahil the Redoubtable Haidout, The Fairy, Bride Boryana, and Dragon’s Wedding) from the perspective of European symbolist drama to emphasize their common aesthetic principles and their specific originality. The comparative analysis thus defined leads to the conclusion that Petko Todorov’s works follows the structural principles of Symbolist drama yet they have their own specifics. The unconventional structure of the dramatic action and dialogue; the wide use of music and painting in the staging of the plays as well as their new genre form make Todorov’s works akin to the francophone Symbolist model. On the other hand, the moral dimension and the pervading national atmosphere in the Bulgarian dramas betray their indebtedness to the Russian Symbolist drama. Finally, the de-valorisation of the fantastic characters and the playing down of Romantic and realistic elements in Petko Todorov’s dramas are totally unknown to the European Symbolist theatre. In this way, Petko Todorov’s dramas are a peculiar combination of Symbolist poetics and influences of the Bulgarian national context. They follow their own development and contribute hereby to the specific evolution of the Bulgarian modernist theatre.
Keywords: European and Slavic symbolist drama; Bulgarian modernist theatre; rewriting; fairy tales; legends